ANALISIS MANFAAT FITUR KESEHATAN DI WRIST-WORN TECHNOLOGY BAGI PENGGUNA - Muhammad Agni Catur Bhakti (PROSIDING SNITek, 2021)
Wearable technology has many options, especially wrist-worn technology. The device can bea smartband, a smartwatch, or a sport watch. Multiple sensors available on this technology enrichedthe data and information transferred to mobilephones via a bluetooth connection. The providedfeatures are not only notifications from smartphones to wrist-worn technology, but also features related with healthy lifestyle information that can be analyzed and researched. The purpose of this research was to determine how optimal these health features were used and beneficial to the users. This research used quantitative method, with non-probability sampling, and voluntary responses sample. It was found from this research that 39.4% of users paid attention to health concern, and 33.3% of users paid moreattention about health concern with wrist-worn technology. Also, 33.3% users stated that technology with health features had good impact on healthy lifestyles, and 30.3% stated the technology had a very good impact.